Resonant three-photon ionization of hydrogenic atoms by a non-monochromatic laser field - Yakhontov, Viktor; Santra, Robin; Jungmann, Klaus (Journal of physics. B, Atomic, molecular and optical physics, 1999)
We present ionization probability and lineshape calculations for the two-step three-photon ionization process, ##IMG## [http://ej.iop.org/images/0953-4075/32/7/006/img6.gif] , of the ground state of hydrogenic atoms in a non-monochromatic laser field with a time-dependent amplitude. Within the framework of a three-level model, the AC Stark shifts and non-zero ionization rates of all states involved were taken into account, together with spatial and temporal inhomogeneities of the laser signal. In contrast with the usual perturbative technique, the time evolution of the atomic states was simulated by directly solving the system of coupled time-dependent inhomogeneous differential equations numerically, the equations being equivalent to the appropriate non-stationary Schrödinger equation. Particular numerical results were obtained for typical parameters of the pulsed laser field that are employed in a new experiment to measure the 1S-2S energy separation with muonium at the Rutherford Appleton Laboratory. The shifts and asymmetries of the photoionization lineshapes revealed may be of relevance for ultra-high-precision experiments in hydrogen in CW laser fields.